Mortalidade fetal: um estudo para os óbitos evitáveis ocorridos no município de Belo Horizonte, 2008-2010 - Heloisa Maria de Assis (2013)
Introduction: The analysis of mortality based on multiple causes of death allows not only disentangle the pattern of mortality in a population, but also the morbidity pattern. Objective: To describe and analyze avoidable stillbirths occurred in Belo Horizonte in 2008-2010, from the perspective of multiple causes and based on the Brazilian list of preventable causes, used as a starting point for the categorization of causes of death. Results: We analyzed 1.369 stillbirths and 546 preventable stillbirths. The analysis of multiple causes of stillbirth indicated that fetal deaths from preventable causes (62.1%) were represented by 45.7% of avoidable deaths preventable through proper care for women during pregnancy; 47.5% of avoidable deaths preventable through adequate care for women in childbirth; 6.2% of avoidable deaths preventable through proper attention to the fetus; and 0.6% deaths preventable through appropriate actions for diagnosis and treatment.Regarding the remaing causes, 31.1% were ill-defined and 6.8% were other causes of death. Moreover, analysis from Two-Step Cluster Method, applied to the 898 preventable stillbirths revealed three clusters: the first cluster was composed mainly by preventable causes reducible by birth care and fetus; the second cluster was formed by preventable causes reducible by attention to pregnancy and illdefined causes and the third cluster was formed from other causes of death, of difficult avoidability. Discussion: The categorization of variables based on the use of Brazilian list of preventable causes pointed out the main problems that healthservices must address in preventing stillbirths. A high proportion of preventable deaths in the present study shows the need for improved prenatal care and childbirth, as well as health policies that focus on comprehensive care to women and childbirth.